Treatment of children with COVID-19: position paper of the Italian Society of Pediatric Infectious Disease - Elisabetta Venturini; Carlotta Montagnani; Silvia Garazzino; Daniele Donà; Luca Pierantoni; Andrea Lo Vecchio; Giangiacomo Nicolini; Sonia Bianchini; Andrzej Krzysztofiak; Luisa Galli; Alberto Villani; Guido Castelli-Gattinara; et al. (BMC, 2020)
Abstract A statement of consensus was formulated after reviewing available literature on pediatric treatment strategies for COVID-19 by the Steering and Scientific Committee of the Italian Society of Infectious Pediatric Diseases in connection with the Italian Society of Paediatrics.